Development of Recombinant Vaccine Using Herpesvirus of Turkey (Hvt) as Vector for Several Viral Diseases in Poultry Industry - Risza Hartawan (Indonesian Center for Animal Research and Development, 2011)
Herpesvirus of turkey (HVT) has been utilised as live vaccine against Marek’s disease in poultry industry world-wide for many years. However, the potency of HVT is not limited on the Marek’s disease only. Along with rapid development of recombinant technique, the potency of HVT can be broaden for other diseases. As naturally apathogenic virus, HVT is a suitable candidate as vector vaccine to express important antigens of viral pathogens. Several researches have been dedicated to design HVT recombinant vaccine by inserting gene of important virus, such as Marek’s disease virus (MDV), immuno bursal disease virus (IBDV), Newcastle disease virus (NDV) and Avian Influenza virus (AIV). Therefore, the future recombinant of HVT has been expected to be better in performance along with the improvement of recombinant technique. Key words: Herpesvirus of turkey, live vector vaccine, viral pathogens